A Study on Progress and Investors' Preception towards Dematerialisation of Shares - Devi, Sudalaimthu S (Gyan Management Journal, 2008)
A depository is an entity, which holds securities of investors in electronic form a t the request of the investors through a registered Depository participant. If an investor wants to utilize the service, offered by a Deposito ry, tlie investor has to open an account with the Depository through a -Depository Participant. The main object ive of a Depository is to minimize the paper work involv d with the ownership, trading and transfer of securities. The minimum net worth stipulated by SEBI for a depository is Rs. 1 00 crore. (B.B. Tandon and A. K. Vashisht)2.The two existing Depositories in India viz.
Keywords: Investors; Dematerialisation; Depositories